The synthesis of (+)-pericosine B - Donohoe, T; Blades, K; Helliwell, M; Waring, M; Newcombe, N (1998)
The first synthesis of (+)-pericosine B is described; this takes seven steps and proceeds in 10% overall yield. The key step in our work is a hydrogen-bonding controlled contra-steric dihydroxylation reaction using osmium tetroxide and an amine promoter. The absolute stereochemistry of the natural product was deduced from the known absolute stereochemistry of our starting material and moreover, the relative and absolute stereochemistry of our synthetic material was determined unambiguously from an X-ray crystal structure of an advanced intermediate.